Extended Wear Silicone Contact Lenses in the Correction of Aphakia - Champagne, D (Canadian Journal of Optometry, 1984)
The following paper is one of several submitted to the CJO by Dr. M. Callender, School of Optometry, University of Waterloo. Written by students in one of his final-year classes, each represents a considerable amount of research and preparatory work in readying the paper for final submission. The editors of the CJO are pleased to present the first of what we hope will be regular submissions by graduating students and their instructors.